2008
DOI: 10.1007/s11284-008-0523-z
|View full text |Cite
|
Sign up to set email alerts
|

Habitat niche specialization in an understory species in a warm temperate forest

Abstract: Relationships between microhabitat variables; understory light conditions in summer and winter, altitude, slope inclination and topographic categories (valley, ridge, and slope) and the distribution of Aucuba japonica Thunb. (Cornaceae), a common understory shrub species in Japan were examined using non-contagious 66, 20 · 20 m 2 quadrats. The Morishita's I d suggested that A. japonica distributions were strongly heterogeneous among the quadrats. Therefore positive spatial autocorrelation of A. japonica at a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
1
0
1
Order By: Relevance
“…This facilitation process occurred between lianas and trees, with existing intensive interspecific competition, in the tropical rainforest (Tang et al 2012). The previous studies have shown that ecologically close species that exhibit a high degree of overlap in some niche dimensions are also able to coexist due to compensating differences in some other niche dimensions (Norberg 2000, Childress et al 2002, while niche differences have long been identified as potential key drivers of species coexistence (Mason et al 2011), and are able to counteract competitive effects and facilitate the coexistence of similar species (Lakkis 1994, Fargione & Tilman 2005, Takeshita et al 2009). In fact, some significant niche differences in temporal (growth period) and spatial levels (plant height) really exist between Phalaris arundinacea and Phragmites communis (Fu et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This facilitation process occurred between lianas and trees, with existing intensive interspecific competition, in the tropical rainforest (Tang et al 2012). The previous studies have shown that ecologically close species that exhibit a high degree of overlap in some niche dimensions are also able to coexist due to compensating differences in some other niche dimensions (Norberg 2000, Childress et al 2002, while niche differences have long been identified as potential key drivers of species coexistence (Mason et al 2011), and are able to counteract competitive effects and facilitate the coexistence of similar species (Lakkis 1994, Fargione & Tilman 2005, Takeshita et al 2009). In fact, some significant niche differences in temporal (growth period) and spatial levels (plant height) really exist between Phalaris arundinacea and Phragmites communis (Fu et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Other tree species prefer specific habitat indicating repellency between different species, which may be the result of long term adaptation to different habitats, different resource usage, and which may explain the niche separation. [4鄄 5,9鄄 12] 。 孙伟中等 [13] 及侯向阳等 [14] 分别对长白山原始红松阔叶林主要树种的空间分布格局进行 了研究。 Hao 等 [15] 及 Wang 等 [16] 以大面积固定样地为基础,对原始红松阔叶林中优势树种不同生长阶段的 空间格局及空间关系进行了分析。 在全球范围内,针对下层木也有学者进行了相关研究。 Takeshita 等在日本 温带森林通过设立 66 个非连续临时样方,分析了光照、地形等生境变量对下层木分布的影响 [17] 。 N覿rhi 等在 芬兰拉普兰德泰加林 119 个点进行了取样调查,分析了土壤养分对下层木树种组成的影响 [18] 。 Ch佗vez 等在 加拿大西部北温带成熟混交林通过设置 10 对监测样方,分析了下层植被不同生长型间相互影响 [19]…”
unclassified
“…Por outro lado, a disponibilidade de luz no sub-bosque da floresta é um dos recursos limitantes em florestas tropicais (Ruger et al 2009), e sua variação espacial e temporal é um componente importante na hipótese de nichos de regeneração (Grubb 1977), no qual plântulas e jovens de diferentes espécies responderiam de maneira distinta à microambientes de luz heterogêneos (Webb & Peart 2000, Daws et al 2005, Takeshita et al 2009. Esta resposta diferencial das espécies em microambientes de luz distintos tem sido frequentemente avaliada enfocando-se na comparação entre espécies pioneiras e tolerantes à sombra, sendo raros os trabalhos que abordem a resposta diferencial a microambientes de luz entre espécies tolerantes à sombra, que são a maioria em florestas tropicais pouco perturbadas (Bloor & Grubb 2003, Daws et al 2005.…”
Section: Introductionunclassified